Evaluation of the Body Composition of Elderly People in the City of Joinville, Santa Catarina, Brazil (Interdisciplinary Studies Journal, 2024)
The aim of the research was to evaluate the body composition of community-dwelling elderly people in the city of Joinville, Santa Catarina. This is a descriptive cross-sectional study involving 250 elderly individuals, consisting of 170 women (132 physically active and 38 sedentary) and 80 men (58 physically active and 22 sedentary). The evaluated variables were age, height, weight, calf and abdominal circumferences, total muscle mass index (TMMI), and body mass index (BMI). The results revealed no significant difference between the groups. However, the high prevalence of overweight/obesity stood out, with 47% among active women and 60.5% among sedentary women. Among active men, it was 63.8%, and among sedentary men, it was 72.7%. This anthropometric characteristic, outside the normal range, was further confirmed by abdominal circumference measurements above average, even in active elderly individuals. It is recommended that programs combining dietary re-education and regular physical exercise be implemented to address this issue, thus promoting more comprehensive health strategies for this special population.
Keywords: Body composition; Nutrition of the elderly; Physical Exercise